Adoptive Immunotherapy Based on Chain-Centric TCRs in Treatment of Infectious Diseases - Kalinina, Anastasiia A. (iScience, 2020)
Complications after vaccination, lack of vaccines against certain infections, and the emergence of antibiotic-resistant microorganisms point to the need for alternative ways of protection and treatment of infectious diseases. Here, we proposed a therapeutic approach to control salmonellosis based on adoptive cell therapy. We showed that the T cell receptor (TCR) repertoire of salmonella-specific memory cells contains 20% of TCR variants with the dominant-active α-chain. Transduction of intact T lymphocytes with the dominant salmonella-specific TCRα led to their enhanced in vitro proliferation in response to salmonella. Adoptive transfer of transduced T cells resulted in a significant decrease in bacterial loads in mice infected with salmonella before or after the adoptive transfer. We demonstrated that adoptive immunotherapy based on T cells, transduced with dominant-specific TCRα could be successfully applied for treatment and prevention of infectious diseases and represent a useful addition to vaccination and existing therapeutic strategies.